Comparison of digital radiography, decalcification, and histologic sectioning in the detection of accessory canals in furcation areas of human primary molars - Poornima P; Subba Reddy V (Wolters Kluwer Medknow Publications, 2008)
Although the terms lateral secondary and accessory canals are often used interchangeably they mean different things. The accessory canal is derived from the secondary canal branching off to the periodontal ligament in apical sections. Different methodology was used to study the accessory canals. Decalcification method appeared to the important in studying the accessory canals as compared to digital radiography and histological sectioning.